Pengaruh Pertumbuhan Ekonomi, Kemiskinan Dan Pengangguran Terhadap Indeks Pembangunan Manusia di Provinsi Gorontalo - Idris, Zulkarnain Ilyas; Mu’jizat, Poppy; Husain, Anggriani (Universitas Negeri Padang, 2024)
Abstract : The purpose of this study was to determine the effect of economic growth, poverty and unemployment on the Human Development Index in Gorontalo Province from 2018–2022. The method used in this research is a quantitative method using the Eviews 12 help panel data regression analysis technique. The model approach used in interpreting the data is the Random Effect Model (REM). The results showed that partially economic growth has no effect on the Human Development Index, Poverty has a negative and significant effect on the Human Development Index and Unemployment has a negative and significant effect on the Human Development Index in Gorontalo Province.Keywords : Human Development Indeks, Economic Growth, Proverty, Unemployment